Importance of age in outcome of oesophagogastroduodenoscopy in open access endoscopy: a profile of patients in Sub-Himalayan region of North India (Faculty of Medicine Universitas Indonesia, 2006)
The Oesophago-Gastro-Duodenoscopy (OGD) is done in patients received by either open access system or the conventional system. The presenting complaints and OGD findings may differ among patients with age < 45 yrs and those who are more than 45 yrs old. The referral diagnosis, age, sex, and environmental factors have important implications on the chances of finding and objective abnormality on endoscopy in a patient. This study was aimed to evaluate to evaluate the profile of 1186 patients divided into younger (<45 yrs) and older age (45 or > 45 yrs) groups presenting for oesophago gastroduodenoscopy through open access referral system in sub-Himalayan region of North India. This is a retrospective study carried out on patients who underwent the OGD from Jan, 2004-Dec, 2004. The study was conducted in Indira Gandhi Medical College situated at a moderate altitude in North India. All patients presenting in Medical College during the study period for OGD were taken into study. The patients were divided into two groups based on age; less than 45 yrs and 45 yrs or more than 45 yrs. Their presenting complaint, age, sex, and OGD findings were recorded. The profile was compared between the two groups. A total of 1186 patients underwent OGD; the females were 451(38%) and males were 735(62%); 616(52%) were < 45 yrs old and 570(48%) of the patients were 45 yrs or older. In the group I 431(70%) had a normal endoscopy and 185(30%) showed abnormal endoscopic findings. In group II 302(53%) had a normal endoscopy, and 268(47%) had abnormal findings on endoscopy. Gastric ulcers, mass lesion/new growth were more common in elderly group, Gastro-esophageal reflux disease (GERD) was more common in younger group. The presenting complaints were similar in both groups. It is concluded that for the same presenting diagnosis the yield of OGD was more in patients > 45 yrs old. The positivity rate increased from 30% in < 45 yrs to 47% in the elderly cohort. So, all people >45 yrs should go for endoscopy at the first hint of upper GI pathology, or appearance of alarm symptoms. (Med J Indones 2006; 15:90-3)